Information and Communication Technology (ICT) as a Tool in Revenue Generation and Tax Administration, A Study of Firs Abakaliki,Ebonyi State-Nigeria (Global Journal of Computer Science and Technology, 2022)
Information and Communication Technology ICT has opened a new visage to globalization in revenue generation and tax administration The deployment and integration of ICT facilities into revenue generation and tax administration for internet access and a web portal implementation that enable the organizations in charge of revenue generation and tax administration in Nigeria federal inland revenue service FIRS to carry out most of its activities ubiquitously on the internet is steadily growing in Nigeria This has enabled many financial operations such as Pay-direct E-tax M-banking E-banking E-fiiling E-assessment E-auditing among others In Nigeria quite a large number of revenue generation and tax administration organizations in different state have either developed their portal or have had one deployed for the purpose of ICT-related operations
Keywords: ICT; renenue generation; tax administration; firs; ebonyi state